2022
DOI: 10.1371/journal.pone.0264792
|View full text |Cite
|
Sign up to set email alerts
|

Association between integrase strand transfer inhibitor (INSTIs) use with insulin resistance and incident diabetes mellitus in persons living with HIV: A systematic review and meta-analysis protocol

Abstract: Introduction Poeple living with HIV have higher prevalence of diabetes mellitus and metabolic perturbations compared to non-HIV populations. Diabetes and metabolic syndrome co-morbidities add significant burden to HIV care. Currently, WHO recommends integrase strand transfer inhibitors (INSTIs) as the first or second line therapy in people with HIV due to overall good tolerability and safety profile. However, whether INSTI use increases the risk of incident diabetes (with or without metabolic syndrome) compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our study was not suited to evaluate associations between incident hypertension and ART (95% of our participants were on the same dolutegravir-based regimen–TLD), however some studies in SSA have found an association between older NRTI, NNRTI and PI agents (namely zidovudine, stavudine, nevirapine, and lopinavir-ritonavir) and hypertension [ 28 , 29 ]. Moreover, the increasingly recognized associations between integrase inhibitors and obesity and other metabolic complications is of concern [ 37 , 38 ], as these conditions tend to predispose invidiuals to hypertension and atherosclerotic cardiovascular (ASCVD) disease possibly increasing cardiovascular-related morbidity and mortality. As > 90% of all PWH in SSA are currently on an integrase based regimen (including participants in our sample), and as HIV is a known independent risk factor for ASCVD-related events, this may be problematic [ 39 – 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study was not suited to evaluate associations between incident hypertension and ART (95% of our participants were on the same dolutegravir-based regimen–TLD), however some studies in SSA have found an association between older NRTI, NNRTI and PI agents (namely zidovudine, stavudine, nevirapine, and lopinavir-ritonavir) and hypertension [ 28 , 29 ]. Moreover, the increasingly recognized associations between integrase inhibitors and obesity and other metabolic complications is of concern [ 37 , 38 ], as these conditions tend to predispose invidiuals to hypertension and atherosclerotic cardiovascular (ASCVD) disease possibly increasing cardiovascular-related morbidity and mortality. As > 90% of all PWH in SSA are currently on an integrase based regimen (including participants in our sample), and as HIV is a known independent risk factor for ASCVD-related events, this may be problematic [ 39 – 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for this systematic review is registered on International Prospective Register of Systematic Reviews database ( CRD42021273040 ) and published. 31 This study is being reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. 32 The link to the study dataset is listed in the online supplemental material (SD).…”
Section: Methodsmentioning
confidence: 99%
“…We explored the relationship of INSTI use with incident diabetes in PWH at population level in an earlier meta-analysis [13], [14]. In that analysis, we demonstrated that the risk of incident DM is actually reduced with INSTI use compared to protease inhibitors and NNRTIs apart from African populations which were largely under-represented.…”
Section: Introductionmentioning
confidence: 99%